Barriers affecting access to health information and health care services among the Deaf Community in Namibia (Journal for Studies in Humanities and Social Sciences, 2020)
Health is a crucial aspect in an individual’s life as it enables people to enjoy their potential as human beings. Consequently there has been an enormous emphasis on equity in access to health care. Just like anybody else, Deaf people have a right to access health information and services and should not be discriminated against in any way. Unfortunately Deaf people are usually marginalised within society and as such their experiences with health care systems across the worldare not readily understood (Scheer, Kroll, Neri & Beatty, 2003). For example, it is assumed that everyone who seeks health service hears and can communicate in a spoken language to receive a standard quality of health care. This study explored the barriers experienced by the Deaf community when accessing health information and health care services in Namibia. The study applied a qualitative approach, and conducted semi-structured interviews with Deaf learners, teachers and other employees in purposefully selected special schools (now known as Resource schools, [MoE, 2013]) and centres for people with disabilities in Namibia. The results indicate that the implementation of regulatory and policy frameworks surrounding disability are still hindered by structural inequalities, social prejudices and stigmatisation of the Deaf community. Therefore, the study recommends changes in the broader structural and social arrangement beyond the health sector if Deaf people are to receive equitable health care.
Keywords: barriers; Deaf community; health; Namibia